Alternative brainwaves and wireless controlled automation of the mobile robots : a case study of wheeled chairs - Aung Myo Myat; Than Lin; Bohez, Erik L.J. (Pathum Thani : Asian Institute of Technology, 2018)
This paper displays an investigation on electroencephalogram (EEG)- based manage of an electricity powered wheelchair.With EEG signals, managing the course of the powered wheel chair is the goal of the project. At the end of the day, this is an endeavor to utilize mind signs to control mechanical gadgets, for example, wheelchairs. To accomplish this objective, we have built up a recursive preparing calculation to produce acknowledgment designs from EEG signals. Our test comes about exhibit the utility of the proposed recursive prepar- ing calculation and the suitability of finishing bearing control of an electric wheelchair by just EEG signals.Abjure headway in control system has empowered the advancement of the wheelchair. This paper proposes wheelchair, an option brainwave control and remote control framework intended for the versatile robot that goes for the all inclusive community who has compactness, arm and leg shortcoming. The control system can be controlled for different applications objects (e.g., auto, flight, differential drive). For various application areas,there are diverse specialized issues that analysts are at present settling.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Mechatronics Engineering, School of Engineering and Technology
Capstone Project (B.Sc.)-Asian Institute of Technology, 2018
Keywords: Mobile robots; Electric wheelchairs; Electroencephalography -- Case studies